Live-in Care Workers in Sheltered Housing for Older Adults in Israel: The New Sheltered Housing Law. Issue 4 (1st October 2016) - Iecovich, Esther
ABSTRACT: Supportive housing schemes were historically aimed to provide group accommodation for older adults. With the aging of residents, facilities were required to enable them to receive care services in order to allow them to age in place. Thus, different countries and different facilities developed different models of housing with care, reflecting cultural and policy diversities. Despite all of the different models, there are many commonalities among the supportive housing schemes across countries. These include provision of dwelling units and care services provided by either the facility or by external agencies. The aims of this article are threefold: to describe the historical development of the ever-evolving supportive care housing phenomena; to point at variations in models of housing and care within the international context; and to present a new Israeli model that enables residents to privately hire live-in care workers to meet their care needs. This is a unique model in the international context that has not been reported before. The article describes the main ideas of the new model and discusses the challenges that it raises and pinpoints the unresolved issues associated with the presence of live-in care workers employed by residents of sheltered housing that should be addressed.